Diagnostic Accuracy of Blood Glucose Measurements in Detecting Venous Compromise in Flaps. Issue 5 (July 2015) - Bashir, Muhammad Mustehsan; Tayyab, Zahid; Afzal, Saira; Khan, Farid Ahmad
<x xml:space="preserve">Abstract</x> Abstract Due to limitations of the current methods for monitoring flap circulation, newer methods with better diagnostic accuracy are needed. A drop in blood glucose levels within flap is a simple method that can be widely used; however, this method has been examined only in small cohorts. The objective of this study was to determine the diagnostic accuracy of blood glucose measurements within flaps in early detection of venous compromise. We sampled 127 pedicled and free flaps, including replants, performed on patients between 12 and 60 years of age. Within flap blood glucose measurements were performed using pinprick and a blood glucose meter at 0, 6, 12, 24 and 48 hours after operation. Daily examination for clinical signs of venous compromise was used to determine flap viability for up to 7th day after operation. Of the 127 flaps, 76 (60%) were performed on men and the mean age ± standard deviation of the patients was 35.8 ± 12.1 years. A cut-off value of 62 mg/dL was determined using a receiver operating characteristic curve. Using this cut-off value, the sensitivity and positive predictive values of within flap blood glucose for determining venous compromise were 90% and 91%, respectively, whereas the specificity and negative predictive values were 78% and 76%, respectively. The overall diagnostic accuracy of within flap blood glucose was 87%. We conclude that blood glucose measurement within flap has acceptable diagnostic accuracy and should be used for early detection of venous compromise.